A longitudinal examination of the interpersonal fear avoidance model of pain: the role of intolerance of uncertainty. Issue 1 (January 2021) - Neville, Alexandra; Kopala-Sibley, Daniel C.; Soltani, Sabine; Asmundson, Gordon J.G.; Jordan, Abbie; Carleton, R. Nicholas; Yeates, Keith Owen; Schulte, Fiona; Noel, Melanie
Abstract : Abstract: Youth with chronic pain and their parents face uncertainty regarding their diagnosis, treatment, and prognosis. Given the uncertain nature of chronic pain and high comorbidity of anxiety among youth, intolerance of uncertainty (IU) may be critical to the experience of pediatric chronic pain. This study longitudinally examined major tenets of the Interpersonal Fear Avoidance Model of Pain and included parent and youth IU as key factors in the model. Participants included 152 youth with chronic pain (Mage = 14.23 years; 72% female) and their parents (93% female). At baseline, parents and youth reported on their IU and catastrophic thinking about youth pain; youth reported on their fear of pain, pain intensity, and pain interference; and parents reported on their protective responses to child pain. Youth reported on their pain interference 3 months later. Cross-lagged panel models, controlling for baseline pain interference, showed that greater parent IU predicted greater parent pain catastrophizing, which, in turn, predicted greater parent protectiveness, greater youth fear of pain, and subsequently greater youth 3-month pain interference. Youth IU had a significant indirect effect on 3-month pain interference through youth pain catastrophizing and fear of pain. The results suggest that parent and youth IU contribute to increases in youth pain interference over time through increased pain catastrophizing, parent protectiveness, and youth fear of pain. Thus, parent and youth IU play important roles as risk factors in the maintenance of pediatric chronic pain over time and may be important targets for intervention. Abstract : Parent and youth intolerance of uncertainty are risk factors in the maintenance of pediatric chronic pain over time and may be important targets for intervention.